ASSOCIATIONS BETWEEN THERAPEUTIC REGIMEN-RELATED FACTORS AND MEDICATION ADHERENCE IN PATIENTS ON ORAL ANTICANCER THERAPY - MIR, SHAKEEL AHMAD (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Objective: Good adherence is critical for successful cancer treatment. Complex medication regimens have been found among the various therapy-related factors causing non-adherence. Methods: In a cross-sectional questionnaire-based study of outpatients, we assessed 75 patients suffering from cancer. The objective of this study is to find associations between therapeutic regimen-related factors and medication adherence in patients on oral anticancer therapy. Results: There was an increase in medication adherence as the length of therapy increased. About 10.76% of the patients with treatment duration <4 years showed low adherence. Low adherence was not observed with treatment duration of more than 4 years. About 6.55% of those taking up to four drugs had low adherence as compared to 14.28% taking more than 4 drugs. About 8.69% of patients taking drugs up to thrice a day showed low adherence as compared to 16.66% taking more than thrice a day. The negative associations between medication regimen complexity and adherence observed in this study were in the predicted direction but did not achieve statistical significance (p>0.05). The effect size was small (d=0.28) Conclusion: Complex prescription regimens reduce adherence to oral anticancer treatments, however, there are several other factors to consider than regimen simplification to increase adherence.